Current debate about the theories of punishment and its impact on the process of judicial individualization - Marín de Espinosa Ceballos, Elena B. (2019)
The present paper describes the current debate about the criminal punishment purpose, as the element that legitimates its imposition. Thus, the author analyses the existent theories to determine how the affect the judicial individualization. As culmination, there is a review of the current practical application of criminal punishment purpose in juridical system, to make some recommendations to be applied.